Relationship of Attention and Memory on Gender Differences (Texas Journal of Multidisciplinary Studies, 2023)
the article reveals the relationship between attention and memory for gender differences according to the study, which partially confirmed the correctness of the hypothesis put forward. As a hypothesis of the study, it was suggested that there are no gender differences in attention and memory, but these differences do exist.